2021
DOI: 10.3390/ma15010016
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Nanocellulose Fortified with Antimicrobial and Anti-Inflammatory Natural Products from Chelidonium majus Plant Cell Cultures

Abstract: In this work we developed a bi-functional Bacterial-Nano-Cellulose (BNC) carrier system for cell cultures of Chelidonium majus—a medicinal plant producing antimicrobial compounds. The porous BNC was biosynthesized for 3, 5 or 7 days by the non-pathogenic Komagataeibacter xylinus bacteria and used in three forms: (1) Without removal of K. xylinus cells, (2) partially cleaned up from the remaining K. xylinus cells using water washing and (3) fully purified with NaOH leaving no bacterial cells remains. The suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, one of the most sought-after characteristics of advanced biologically active materials is antimicrobial activity, which BC itself lacks. Therefore, BC is commonly modified with divergent antimicrobial agents, such as metal/metal oxide nanoparticles, antibiotics, and organic compounds (e.g., amino acids, curcumin, chitosan,…) (Zielińska et al 2022;Krasowski et al 2021;Moritz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the most sought-after characteristics of advanced biologically active materials is antimicrobial activity, which BC itself lacks. Therefore, BC is commonly modified with divergent antimicrobial agents, such as metal/metal oxide nanoparticles, antibiotics, and organic compounds (e.g., amino acids, curcumin, chitosan,…) (Zielińska et al 2022;Krasowski et al 2021;Moritz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2022) reported that HS broth pH (6.0), inoculated by 5% (v/v) from the strain Komagataeibacter maltaceti P285 then incubated at temperature 30°C for about 7 day, after cultivation, cellulose harvested then purified with high productivity. This medium was also used by Zieli´nska et al (2022) to produce high amounts of BC from another strain of AAB; K. xylinus. The nanocellulose termed as bacterial cellulose (BC) which produced through the bottom up, approach use the fermentation of low mwt.…”
Section: Bnc Produced By Acetic Acid Bacteriamentioning
confidence: 99%
“…C. majus cells were used as a model system for the production of protoberberine, protopine and benzophenanthridine derivatives. The plant cells were cultured on bacterial nanocellulose (BNC) carriers 1 . To enhance biosynthesis, three strains of microorganisms, i.e., Candida albicans, Staphylococcus aureus and Pseudomonas aeruginosa were inoculated at the top or the bottom of BNC discs.…”
mentioning
confidence: 99%